2011
DOI: 10.1590/s0101-31222011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica de sementes de caesalpinia pyramidalis tul: durante o armazenamento

Abstract: A catingueira (Caesalpinia pyramidalis Tul.) é uma espécie arbustiva de ampla dispersão no semiárido nordestino e endêmica do bioma caatinga. A irregularidade e má distribuição das chuvas na região comprometem a produção de sementes, a tal ponto que a maioria dos frutos apresenta sementes mal formadas ou inviáveis para a germinação. Dessa forma, o presente trabalho objetivou estudar o comportamento das sementes de Caesalpinia pyramidalis Tul., acondicionadas em diferentes embalagens e ambientes de armazenament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(4 reference statements)
0
2
0
3
Order By: Relevance
“…As such, considerable effort has been directed towards maintaining their physiological quality and prolonging their longevity (including monitoring their water content and controlling environmental temperatures and storage conditions) (NAGEL; BÖRNER, 2010). Oliveira et al (2011a) and Silva et al (2011) reported that adequate storage can maintain higher seed viability and vigor than would normally be possible under natural conditions, and the types of packaging materials used, the temperatures and relative humidity of the storage environments play important roles in maintaining seed physiological quality. Oliveira et al (2011b) observed that some species of native Brazilian fruits, the genus Campomanesia (MYRTACEAE), have significant commercial potential due to their desirable agroeconomic characteristics such as high productivity and high brix values.…”
Section: Introductionmentioning
confidence: 99%
“…As such, considerable effort has been directed towards maintaining their physiological quality and prolonging their longevity (including monitoring their water content and controlling environmental temperatures and storage conditions) (NAGEL; BÖRNER, 2010). Oliveira et al (2011a) and Silva et al (2011) reported that adequate storage can maintain higher seed viability and vigor than would normally be possible under natural conditions, and the types of packaging materials used, the temperatures and relative humidity of the storage environments play important roles in maintaining seed physiological quality. Oliveira et al (2011b) observed that some species of native Brazilian fruits, the genus Campomanesia (MYRTACEAE), have significant commercial potential due to their desirable agroeconomic characteristics such as high productivity and high brix values.…”
Section: Introductionmentioning
confidence: 99%
“…This could be related to increased respiration rate and intrinsic biological factors proper to each seed type (Almeida et al, 1999;Carvalho and Nakagawa, 2012). Experiments with seeds of Copaifera multijuga and Caesalpinia pyramidalis, kept in impermeable packages showed similar pattern in storage (Silva et al, 2011;Oliveira et al, 2011). The analysis of variance for physiological seed quality of quinoa during storage showed that environment (E), packaging (P), period (PE) and the interactions ExP and ExPE had an effect on all observations (p<0.05).…”
Section: Resultsmentioning
confidence: 74%
“…Sendo assim, as sementes provenientes da borda toleraram melhor o armazenamento mantendo o poder germinativo por aproximadamente seis meses. Oliveira et al (2011) também estudaram o armazenamento de sementes de P. pyramidalis, sem considerar o efeito borda e concluíram que a viabilidade e o teor de água das sementes foram mantidos durante o período avaliado (225 dias).…”
Section: Ambiente Presença De Proximal Ausência De Proximalunclassified